OSA Treatment Lowers the Risk of Declining Daily Activities - Huhtakangas, Jaana K.; Huhtakangas, Juha; Haapea, Marianne; Saaresranta, Tarja (Elsevier, 2026)
Background
The aim of the study was to investigate whether severe obstructive sleep apnea (OSA) had association with quality of life (QOL), fatigue and functional ability seven years after ischemic stroke.
Methods
A total of 204 ischemic stroke patients were included in the study during 2013‐2015. After seven years the 136 survivors had a structured interview by telephone focusing on subjective QOL, functional ability, fatigue, depression, and insomnia.
Results
Of alive patients, 136/99.3% answered the questionnaires. The mean age was 64.2 years, 41.9 % were men, and 54/40% had respiratory event index (REI) ≥30/h. Those with REI ≥ 30 were more obese (29.2% vs 26.6%, p < 0.001), and coronary artery disease (25.9% vs 12.2%, p = 0.04), had lower Barthel Index (BI) (88.3 vs 92.3, p = 0.014), higher modified Rankin Scale (mRS) (2 vs 1, p = 0.025), and more need of medical aids (18.4 vs 13.2, p = 0.004). The QOL was good, but lower (6.98 vs 6.48, p = 0.056) and mobility domain was significantly worse (1.5 vs 1.3, p = 0.019) among severe OSA (REI) ≥30/h) patients. The CPAP treatment associated with an impaired risk of decreased usual activities (OR 0.190, 95% CI 0.042‐0.857, p = 0.031). Though severe OSA was not an independent risk factor for functional ability, whereas higher BMI was an independent risk factor for impaired QOL (p = 0.006, 95%CI 1.047‐1.315).
Conclusions
Seven years post-stroke the QOL was in good level, although it tended to be lower in stroke patients with severe OSA. The CPAP treatment associated with better usual activities in patients with severe OSA.